THE DIGITALIZATION OF CULTURE THROUGH ASSISTANCE IN CREATING THE PURANA JERO PANDAK WEBSITE, PANDAK GEDE VILLAGE, TABANAN - , I Komang Try Adi Stanaya; Meitridwiastiti, Anak Agung Ayu; Atmaja, I Gusti Bagus Agung Kusuma; Dharma, Komang Ari Setya; Susena, I Gde Jananuraga; Diaz, Katharina (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
Talking about culture cannot be separated from a legacy of past life passed down from generation to generation. Culture is a key element and plays an important role in sustainable living. It is an integral part of life in every country, shaped by the environment, social situations, and economic factors. The function of culture goes beyond serving as an identity; it also acts as a lifestyle and a guide for society. Today, culture is known personally by its owners and can be widely recognized by anyone through technological intermediaries. In this regard, technology is inseparable from the language used in its presentation. With technological advances, language and culture can be significantly shaped and transformed. The Jero Pandak family owns cultural artifacts, namely the Purana Jero Pandak and keris (traditional Indonesian daggers). The Purana Jero Pandak tells the origins of the family's ancestors, who possess 13 keris. The community partner aims for this cultural heritage to be recognized by the older or previous generations and serve as a means of education or learning about history and cultural heritage for the younger generation of the Jero Pandak family and society in general. This is expected to enhance understanding of the family's history and the details of the keris they own. Through digitalization in the form of a website, it is hoped to positively introduce this cultural heritage and highlight the importance of preserving and maintaining cultural aspects from extinction due to the younger generation's lack of knowledge. This community service activity aims to document the purana and keris that have been passed down in digital form via a website. Through this community service, there is a positive change in education and communication regarding the origins and history of the ancestors of the extended family. This is expected to lead in a more advanced, connected, and inclusive direction.